Effect of childhood trauma on disease severity in patients with fibromyalgia: The mediating role of psychological resilience - Özlem Kazan Kızılkurt; Arda Kazım Demirkan; Ferzan Ergün Gıynaş; Hüseyin Güleç (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the effect of childhood traumas on the disease severity in fibromyalgia and evaluate the mediating role of psychological resilience in this effect. Patients and methods: Between June 2017 and January 2018, this study included a total of 80 female patients (mean age: 31.9±4.0 years; range, 20 to 40 years) with fibromyalgia according to the 2010 American College of Rheumatology fibromyalgia diagnostic criteria. All patients were evaluated using the sociodemographic data form, Resilience Scale for Adults (RSA), Childhood Trauma Questionnaire (CTQ), and Fibromyalgia Impact Questionnaire (FIQ). Results: A positive correlation was observed between the FIQ and CTQ total scores, emotional abuse, physical abuse, and physical neglect scores. The FIQ was negatively correlated with the RSA scores. Path analysis conducted to evaluate mediating effect of psychological resilience revealed that psychological resilience had a mediator role in the correlation between FIQ and emotional abuse, physical abuse, and physical neglect scores. Conclusion: The main finding of this study is the protective effect of psychological resilience -improvable capacity to cope with early life traumas- on fibromyalgia symptoms that leads to negative functioning of several aspects.